Answer:
To prove the given identity, we can start by multiplying both sides of the equation by (cosθ - sinθ) to obtain:
(cosθ/1 - tanθ) (cosθ - sinθ) - sin^2θ/(cosθ - sinθ) = (cosθ + sinθ)(cosθ - sinθ)
Expanding both sides of the equation gives us:
cos^2θ - tanθcosθ - sin^2θ = -sin^2θ + cos^2θ
We can simplify this equation to:
-tanθcosθ = -sin^2θ + cos^2θ
We can simplify this further by using the identity cos^2θ + sin^2θ = 1:
-tanθcosθ = 1 - 2sin^2θ
We can rearrange this equation to solve for sin^2θ:
sin^2θ = (1 + tanθcosθ)/2
This is the desired result, so we have successfully proved the given identity.
I hope this helps! Let me know if you have any questions.
Explanation:
SELF EXPLANATORY